Migration towards Europe and the “welfare magnet” : “Determinants of Turkish Migration to EU-15” - Jedličková, Kristýna (2015)
The purpose of this thesis is to analyse which factors drive migration from Turkey towards Europe and whether the welfare benefits play a major role in the decision making process. The analysis is based on a gravitation model of migration in log-log form. The FE and RE methods were employed as estimation techniques and the Hausman test enabled to distinguish them. The present problem of heteroscedasticity was solved by adjusting the model with robust standard errors. The most important determinants appear to be individual income which immigrants can earn in the states of the EU-15 and welfare benefits provided by the EU-15. The number of acquisition of citizenship, as a proxy for migration policy of countries the EU-15, plays also important role. The limitation of the model is that the rest of the variables are not statistically significant and therefore we do not consider them as important determinants.